1996
DOI: 10.1149/1.1837034
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanism of Porous Nickel Oxide in Molten Li/K Carbonates

Abstract: Many concerns have been raised concerning the mechanism whereby the thickness of electrodes in molten carbonate fuel cells is reduced over time. We reported in a previous paper that when CO2 partial pressure in the atmospheric gas is low and the temperature of molten carbonates is high, porous nickel oxide deforms easily under compressive stress. In this paper, the mechanism of cathode deformation, which has not yet been clarified, was investigated. Results indicate that cathode deformation occurs when particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The reduction of NiO (NiO + H 2 → Ni + H 2 O) is a reaction with high important technological significance, not only as a source of Ni from Ni ores but also due to its importance in catalytic reactions. , From the basic point of view, the reduction of NiO is regarded as a model reaction due to its single-stage transformation fuel cell electrodes, gas sensors, or supercapacitors/battery hybrids but also for their magnetic properties since NiO is antiferromagnetic and Ni ferromagnetic. In addition, metal−ceramic materials are also interesting since they typically exhibit enhanced mechanical properties . The methods usually employed for the reduction process are based on high-temperature treatments under H 2 atmosphere. , These studies show that the reaction is strongly influenced by the concentration of defects, in particular oxygen vacancies, in the starting material.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of NiO (NiO + H 2 → Ni + H 2 O) is a reaction with high important technological significance, not only as a source of Ni from Ni ores but also due to its importance in catalytic reactions. , From the basic point of view, the reduction of NiO is regarded as a model reaction due to its single-stage transformation fuel cell electrodes, gas sensors, or supercapacitors/battery hybrids but also for their magnetic properties since NiO is antiferromagnetic and Ni ferromagnetic. In addition, metal−ceramic materials are also interesting since they typically exhibit enhanced mechanical properties . The methods usually employed for the reduction process are based on high-temperature treatments under H 2 atmosphere. , These studies show that the reaction is strongly influenced by the concentration of defects, in particular oxygen vacancies, in the starting material.…”
Section: Introductionmentioning
confidence: 99%
“…9 We also reported that the lithiation of porous NiO resulted in the growth of fine Li-NiO crystals on the NiO grain surface and the change in the crystal grain form and the porous structure depending on CO 2 partial pressure and compressive stress. 10 For the coating with LiCoO 2 , it is desirable that when Ni or NiO is lithiated, its fine crystals are also coated with LiCoO 2 uniformly. Furthermore, the LiCoO 2 coating layer must follow the changes in grain conditions and structure.…”
mentioning
confidence: 99%